Synthesis, Biological, and Computational Evaluation of Antagonistic, Chiral Hydrobenzoin Esters of Arecaidine Targeting mAChR M1 - Marius Ozenil (Pharmaceuticals, 2020)
Muscarinic acetylcholine receptors (mAChRs) are a pivotal constituent of the central and peripheral nervous system. Yet, therapeutic and diagnostic applications thereof are hampered by the lack of subtype selective ligands. Within this work, we synthesized and chemically characterized three different stereoisomers of hydrobenzoin esters of arecaidine by NMR, HR-MS, chiral chromatography, and HPLC-logP. All compounds are structurally eligible for carbon-11 labeling and show appropriate stability in Dulbecco’s phosphate-buffered saline (DPBS) and F12 cell culture medium. A competitive radioligand binding assay on Chinese hamster ovary cell membranes comprising the human mAChR subtypes M1-M5 showed the highest orthosteric binding affinity for subtype M1 and a strong influence of stereochemistry on binding affinity, which corresponds to in silico molecular docking experiments. Ki values toward M1 were determined as 99 ± 19 nM, 800 ± 200 nM, and 380 ± 90 nM for the (R,R)-, (S,S)-, and racemic (R,S)-stereoisomer, respectively, highlighting the importance of stereochemical variations in mAChR ligand development. All three stereoisomers were shown to act as antagonists toward mAChR M1 using a Fluo-4 calcium efflux assay. With respect to future positron emission tomography (PET) tracer development, the (R,R)-isomer appears especially promising as a lead structure due to its highest subtype selectivity and lowest Ki value.